Relationships between needs satisfaction and the quality of motivation with academic engagement in pre-service physical education teachers. - López García, Ginés David; Carrasco-Poyatos, María; Burgueño, Rafael; Granero-Gallegos, Antonio (Sage, 2023)
Building upon self-determination theory, the objective of this research was to examine the predictive associations of pre- service physical education (PE) teachers’ basic psychological need satisfaction (i.e., autonomy, competence, relatedness, and novelty) with their academic engagement via the quality of their motivation. A purposive sample of 920 pre-service PE teach- ers (569 men and 351 women; Mage = 24.73; SD= 5.34) participated in this cross-sectional research. The results from struc- tural equation modeling revealed that autonomy, competence, and novelty satisfaction positively predicted autonomous motivation, and negatively predicted amotivation. While competence satisfaction positively predicted controlled motivation, novelty satisfaction did it negatively. Autonomous motivation and controlled motivation positively predicted academic engagement, while amotivation was negatively associated with it. This research underscores the importance of considering pre-service PE teachers’ autonomy, competence, and, specially, novelty satisfaction in promoting their autonomous motiva- tion and academic engagement in initial teacher education program
Keywords: Investigación activa en educación; Profesores - Formación profesional; Educación física - Estudio y enseñanza; Need-based experiences; Behavioral regulation; Self-determined motivation; Student teacher; Teacher training